2014
DOI: 10.5507/bp.2013.090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-glucan on some environmental toxins: An overview

Abstract: Background. Beta-glucans are naturally occurring polysaccharides and constituents of the cell wall of certain pathogenic bacteria and fungi. They have proven healing and immunostimulating properties, linked to enhanced macrophage and natural killer cell function which likely involves specific interaction with several cell surface receptors, such as lactosylceramide, selected scavenger receptors, and dectin-1 (betaGR). In particular, glucan reduces the immunosuppressive effects of a number of agents including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, it is also known that the cell wall of yeast is composed of complex polymers β- d -glucans, α-mannans, α-mannoprotein and a minor amount of chitin, all of which have a number of bioprotective properties [ 29 ]. In the specific case of glucan, this polysaccharide has caught scientific attention, mainly due to its immunomodulatory capacity, which has been demonstrated in some studies to decrease the immunosuppressive actions of various immunotoxins, including mercury and perluoroctanic acid [ 30 ]. Similarly, field studies related to his genotoxicity, antigenotoxicity and chemoprevention capacity have increased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is also known that the cell wall of yeast is composed of complex polymers β- d -glucans, α-mannans, α-mannoprotein and a minor amount of chitin, all of which have a number of bioprotective properties [ 29 ]. In the specific case of glucan, this polysaccharide has caught scientific attention, mainly due to its immunomodulatory capacity, which has been demonstrated in some studies to decrease the immunosuppressive actions of various immunotoxins, including mercury and perluoroctanic acid [ 30 ]. Similarly, field studies related to his genotoxicity, antigenotoxicity and chemoprevention capacity have increased.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Jayasekara et al [62] and Anusuya and Sathiyabama [140] reported the antifungal efficacy of β-D glucan against the Saccharomyces cerevisiae strain and in the prevention of rhizome rot disease of turmeric, respectively. Vetvicka [141] examined the impact of β-glucan against environmental toxins like mycotoxin, aflatoxin, and depleted uranium.…”
Section: Microbial β-Glucanmentioning
confidence: 99%
“…Meanwhile Narusaka et al [12] stated that yeast cell walls extracted from S. pastorianus containing ±40% mannoprotein, 60% β-glucan, and 1.3% chitin could inhibit the growth of the fungus Colletotrichum higginsianum by activating resistance to fungi through the Salicylic Acid (SA)-dependent pathway. β-glucan has been found to have a role in decontaminating toxin that remain in the environment including in water, with the advantages that the toxicity is biologically reduced, saving mammalian cells [21,22]. Meanwhile, β-glucan and its cationic derivatives show decontamination effects by means of their polycation structure, which easily react with the fungi's biological membrane, and show antifungal activities [22].…”
Section: Introductionmentioning
confidence: 99%
“…Glucans can not only play a role in mycotoxin absorption but can also directly reduce aflatoxin production. (1,3)-β-D-glucan with side chain (1,6)-β-D-glucan can regulate the presence of aflatoxin [21].…”
Section: Introductionmentioning
confidence: 99%